Análise de assunto das imagens dos cartões-postais do acervo Alaíde Lisboa de Oliveira: o uso do Aboutness e do Ofness na extração dos conceitos - Nina Cláudia Mendonça Campos de Miranda (2019)
The complexity of the process of indexing image documents has awakened, among professionals in the area of treatment and organization of information, greater attention and care with thematic representation. The focus of this study was to analyze the first stage of the indexing of postcards: the analysis of the subject, which means identifying which is the subject addressed in the document. The subject analysis covers the reading of the document, the extraction of concepts and the identification of Ofness and Aboutness. The research presented the postcard image document of the Alaíde Lisboa de Oliveira Collection, of the Library of the Faculty of Education of the Federal University of Minas Gerais. The main objective of this study was to investigate if the use of the concepts of Aboutness and Ofness can contribute to guide the librarian in the subject analysis of postcard images in the extraction of concepts. An empirical study was carried out involving two librarians from the UFMG Library System to index the images of three postcards in two stages. The first stage comprised the analysis of a free subject and the second, the analysis of a guided subject, using a new possibility of systematization of the subject analysis, based on the methodology of the concepts of Aboutness and Ofness developed by Shatford (1986). The exploration of the data showed that the subject analysis of imaging documents should be more detailed, careful and judicious. It was observed that librarians met the requirements when analyzing the images using the subject analysis system proposed to describe the images. It was concluded that the concepts that underpinned the proposed methodology served as guidelines for librarians, because following step by step the selection of generic and specific Ofness it is possible to understand the description of the images, with the organization of ideas in detailing the elements portrayed in the images, to determine the Aboutness in another phase and thus choose the relevant descriptors for users.